2008
DOI: 10.1111/j.1600-0404.2007.00984.x
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C expression in ischemic white matter lesions

Abstract: These results suggest that low levels of CSF cystatin C in ischemic WMLs might be due to the decreased number of astrocytes that secrete cystatin C in response to the stimuli of proteases and inflammatory cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…However, higher levels of serum cystatin C have also been associated with cognitive decline34 35 and with WML36 in large population-based cohort studies. In WML, the cystatin C expression is upregulated in astrocytes, presumably due to a self-defence response in the process of white matter degeneration37 Our results, based on EV -cystatin C, show similar results as increasing EV-cystatin C is related to increased volume of WML. Cystatin C is secreted by all human tissues38 which presumably concomitantly shed cystatin C + EVs in order to directly influence more distant processes.…”
Section: Discussionsupporting
confidence: 81%
“…However, higher levels of serum cystatin C have also been associated with cognitive decline34 35 and with WML36 in large population-based cohort studies. In WML, the cystatin C expression is upregulated in astrocytes, presumably due to a self-defence response in the process of white matter degeneration37 Our results, based on EV -cystatin C, show similar results as increasing EV-cystatin C is related to increased volume of WML. Cystatin C is secreted by all human tissues38 which presumably concomitantly shed cystatin C + EVs in order to directly influence more distant processes.…”
Section: Discussionsupporting
confidence: 81%
“…Umegae et al . reported that CysC is upregulated in regressive astrocytes in a self‐defense response to the process of white matter degeneration in patients with WMH . Levy et al .…”
Section: Discussionmentioning
confidence: 99%
“…Umegae et al reported that CysC is upregulated in regressive astrocytes in a self-defense response to the process of white matter degeneration in patients with WMH. 28 Levy et al showed that CysC colocalized with amyloid-beta in parenchymal and vascular amyloid deposits in AD patient brains. 29 Furthermore, Sun et al reported that CysC regulates soluble amyloid-beta levels and is subsequently associated with neuronal deficits in a mouse model of AD.…”
Section: Discussionmentioning
confidence: 99%
“…As multiple biological activities of CysC were found in the brain, much attention has been given to the relationship between CysC and the cause of neurological disease. In ischaemic WMLs, the CysC expression is upregulated in the regressive astrocytes, possibly a self-defense response in the process of white matter degeneration [23]. CysC regulates the extracellular matrix turnover resulting in the progressive formation of a cerebral arterial aneurysm [24].…”
Section: Discussionmentioning
confidence: 99%